The impact of COVID-19 on dual career athletes: Three typologies of coping - Cartigny, E.; Vickers, E.; Harrison, G.; Appleby, R.; McCullogh, N. (Journal of Sports Sciences, 2022)
This research aimed to understand the coping and wellbeing of dual-career athletes during the COVID-19 pandemic. A total of 159 dual-career athletes completed a series of questionnaires that aimed to identify the coping strategies and their impact on the wellbeing of respondents during COVID-19 restrictions. The survey included measures of coping, wellbeing, burnout, and identity along with open-ended questions with the focus of change, coping, and support. Findings identified three coping approaches that have been employed by dual-career athletes: positive coping, negative coping, and acceptance. The three coping approaches also showed distinct wellbeing and burnout profiles. The negative coping group showed high indicators of burnout and poor wellbeing, whereas the acceptance group showed the highest scores on wellbeing and low indications of burnout. Based on the findings, it is recommended that dual-career support providers and stakeholders consider how best to support athletes that have not coped well and have experienced wellbeing issues during this time. It is also important to recognise the benefit a dual-career has provided to some individuals during this period.